Mechanisms of resistance to chemotherapeutic and anti-angiogenic drugs as novel targets for pancreatic cancer therapy - Tamburrino, Anna; Piro, Geny; Carbone, Carmine; Tortora, Giampaolo; MELISI, Davide (Frontiers in Pharmacology, 2013)
Pancreatic cancer remains one of the most lethal and poorly understood human malignancies and will continue to be a major unsolved health problem in the 21st century. Despite efforts over the past three decades to improve diagnosis and treatment, the prognosis for patients with pancreatic cancer is extremely poor with or without treatment, and incidence rates are virtually identical to mortality rates. Although advances have been made through the identification of relevant molecular pathways in pancreatic cancer, there is still a critical, unmet need for the translation of these findings into effective therapeutic strategies that could reduce the intrinsic drug resistance of this disease and for the integration of these molecularly targeted agents into established combination chemotherapy and radiotherapy regimens in order to improve patients’ survival. Tumors are heterogeneous cellular entities whose growth and progression depend on reciprocal interactions between genetically altered neoplastic cells and a non-neoplastic microenvironment. To date, most of the mechanisms of resistance studied have been related to tumor cell-autonomous signaling pathways. However, recent data suggest a putative important role of tumor microenvironment in the development and maintenance of resistance to classic chemotherapeutic and targeted therapies. This present review is meant to describe and discuss some of the most important advances in the comprehension of the tumor cell-autonomous and tumor microenvironment- related molecular mechanisms responsible for the resistance of pancreatic cancer to the proapoptotic activity of the classic chemotherapeutic agents and to the most novel antiangiogenic drugs. We present some of the emerging therapeutic targets for the modulation of this resistant phenotype.